The Effect of the Angiotensin-Converting Enzyme Inhibitor on Bone Health in Castrated Hypertensive Rats Is Mediated via the Kinin-Kallikrein System - Zhang, Na; Huo, Yanan; Yao, Chen; Sun, Jie; Zhang, Yafeng (Journal of the Renin-Angiotensin-Aldosterone System, 2022)
Background. In previous studies, angiotensin-converting enzyme inhibitor (ACEI) use was associated with increased bone loss, while an angiotensin II type I receptor blocker had no effect on bone loss in elder subjects, which suggested that the effect of ACEI on bone loss was not mediated through the classical renin-angiotensin system. In this study, we set to investigate whether the effect of ACEI on bone deterioration was mediated via the kinin-kallikrein system. Methods. Six-month-old male and female spontaneously hypertensive rats were used. The effect of captopril on blood pressure, serum Ang II, and bradykinin concentration was measured in intact rats. Ovariectomy and orchidectomy were performed to establish an osteoporosis model in female and male rats, respectively. Captopril and the bradykinin receptor blocker icatibant (HOE140) were administered after operation for 12 weeks. Serum Ang II and bradykinin concentration, bone turnover markers, bone mineral density (BMD), and bone microarchitecture were evaluated. Femur samples were subjected to a mechanical test. Results. Captopril decreased blood pressure and serum Ang II concentration and increased serum bradykinin concentration in intact rats (P<0.05). After castration, captopril decreased serum Ang II concentration (P<0.05); in female rats, icatibant increased serum Ang II concentration (P<0.05). Captopril increased serum bradykinin concentration (P<0.05); in male rats, icatibant decreased serum bradykinin concentration (P<0.05). Captopril increased the rat urine deoxypyridinoline-creatinine ratio (DPD/Cr) and serum osteocalcin concentration (P<0.05). Icatibant decreased urine DPD/Cr in male rats (P<0.05) and increased osteocalcin concentration in female rats (P<0.05). Captopril increased cancellous BMD in castrated hypertensive rats (P<0.05), and icatibant further increased cancellous BMD (P<0.05), which was due to the increased trabecular bone number. In mechanical testing, ACEI increased bone strength (P<0.05), and icatibant further improved it (P<0.05). Conclusion. ACEI decreased bone deterioration in both male and female hypertensive rats, and the bradykinin receptor blocker further decreased bone deterioration.